2012
DOI: 10.3319/tao.2012.02.29.01(tt)
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Vertical Velocity Field of Southernmost Longitudinal Valley in Eastern Taiwan: A Joint Analysis of Leveling and GPS Measurements

Abstract: In order to provide a detailed vertical velocity field in southernmost Longitudinal Valley where shows a complex threefault system at the plate suture between Philippine Sea plate and Eurasia, we conducted leveling and GPS measurements, compiled data from previous surveys and combined them into a single data set. We compiled precise leveling results from 1984 to 2009, include 5 E-W trending and one N-S trending routes. We calculated the GPS vertical component from 10 continuous stations and from 89 campaign-mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…(b) Shaded relief map of the area outlined in Figure 6a with configuration of major active faults on land from Chen et al . [] and the zone of inferred strike‐slip offshore based on our analyses shown as pairs of half arrows. Contours of elevation change shown in color (see key).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(b) Shaded relief map of the area outlined in Figure 6a with configuration of major active faults on land from Chen et al . [] and the zone of inferred strike‐slip offshore based on our analyses shown as pairs of half arrows. Contours of elevation change shown in color (see key).…”
Section: Discussionmentioning
confidence: 99%
“…Coseismic subsidence during the 2006 Peinan M w 6.7 earthquake was localized in the valley north of Taitung and at the southern termination of the Coastal Range northeast of Taitung [ Chen et al ., ]. Long‐term GPS data from this region processed to remove the effects of the Peinan earthquake [ Chen et al ., ] likewise reveal subsidence localized at the southern end of the Longitudinal Valley and Coastal Range (see orange and red contour lines in Figure b). These data also indicate rapid uplift to the north where ongoing collision is well documented (see blue and purple contour lines in Figure b).…”
Section: Discussionmentioning
confidence: 99%
“…One major advantage of singlefrequency GPS is that the cost of hardware is much 1 Velocity field of the near-fault GPS array in the Taitung area. The left graph shows the vertical velocities (Chen et al, 2012) and the right graph presents the horizontal velocities relative to the ITRF2005 reference frame (Chen et al, 2013). Black lines represent major active faults: Chihshang Fault (1), Lichi Fault (2) Networks of L1 GPS receivers mixed with dualfrequency receivers have been previously proposed and tested in active fault zones and for volcano monitoring systems with encouraging results (Chen, 2001;Roberts, 2002;Rizos, 2002).…”
Section: Instrumentation and General Characteristicsmentioning
confidence: 93%
“…The convergence rate is about 8.2 cm/year, while one-third of horizontal shortening of about 3 cm/year is being absorbed across the southern LV (Yu et al, 1990;Yu and Kuo, 2001). Recent global positioning system (GPS) and precise levelling results from mostly campaign-mode surveys combined with 10 continuously operating reference stations (CORS) indicated that the velocity fields of horizontal and vertical components vary in different faults and in different locations in this area (Chen et al, 2012;Chen et al, 2013) (Fig. 1).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation